Association between statin use and the risk of gout in patients with hyperlipidemia: A population-based cohort study - Lin, Guan-Ling; Lin, Hsiu-Chen; Lin, Hsiu-Li; Keller, Joseph Jordan; Wang, Li-Hsuan (Frontiers in Pharmacology, 2023)
Objective: To investigate the association between statin use and risk of gout in patients with hyperlipidemia. Methods: In this population-based retrospective cohort study, patients ≥20 years and diagnosed as having incident hyperlipidemia between 2001 and 2012 were identified from the 2000 Longitudinal Generation Tracking Database in Taiwan. Regular statin users (incident statin use, having 2 times and ≥90 days of prescription for the first year) and two active comparators [irregular statin use and other lipid-lowering agent (OLLA) use] were compared; the patients were followed up until the end of 2017. Propensity score matching was applied to balance potential confounders. Time-to-event outcomes of gout and dose- and duration-related associations were estimated using marginal Cox proportional hazard models. Results: Regular statin use non-significantly reduced gout risk compared with irregular statin use (aHR, 0.95; 95% CI, 0.90–1.01) and OLLA use (aHR, 0.94; 95% CI, 0.84–1.04). However, a protective effect was noted for a cumulative defined daily dose (cDDD) of >720 (aHR, 0.57; 95% CI, 0.47–0.69 compared with irregular statin use and aHR, 0.48; 95% CI, 0.34–0.67 compared with OLLA use) or a therapy duration of >3 years (aHR, 0.76; 95% CI, 0.64–0.90 compared with irregular statin use and aHR, 0.50; 95% CI, 0.37–0.68 compared with OLLA use). Dose- and duration-dependent associations were consistent in the 5-year sensitivity analyses. Conclusion: Although statin use was not associated with a reduction in gout risk, the protective benefit was observed in those receiving higher cumulative doses or with a longer therapy duration.